Efficacy and safety of low dose Methotrexate in the treatment of chronic hand eczema - Ghosh, Nandita; Nasrin, Tabassum; Mahmud, Hasan; Paul, Harasit Kumar (Journal of Pakistan Association of Dermatologists, 2020)
Background Hand eczema is often a chronic, multifactorial disease which has enormous socioeconomic consequences and a massive impact on patients' quality of life. Objective To assess the efficacy and safety of low-dose oral methotrexate in patients of chronic hand eczema. Materials and Method This randomized controlled trial was carried out in the Department of Dermatology and Venereology, Bangabandhu Sheikh Mujib Medical University, Dhaka from July 2013 to January 2014. In this study, we enrolled 66 patients through purposive sampling, out of which 33 patients were enrolled in group-A (Study-group) who were treated with low dose oral methotrexate (MTX) in a dose of 0.1 mg/kg body weight once weekly for three months and 33 patients were in group-B (Control group) who underwent therapy with topical clobetasol propionate (0.05%) 2 times daily for 2 weeks then every alternate day for up to three months. The effects of treatment were evaluated using Hand Eczema Severity Index (HECSI) score at base line and at twelfth week and the side effects were unveiled by history, clinical examination and laboratory investigations. Results In this study male and female ratio was 1: 1.08. At baseline, mean HECSI score in group-A and group-B were 24.51 (±17.33) vs. 21.50 (±18.40). At 12th week follow up mean HECSI score in group-A 6.00 (±4.93) and that of in group-B was 1.07 (±0.39) which was statistically highly significant (p<0.0001). In group-A, mean HECSI scores at baseline and at 12th week follow up were 24.51 (±17.33) and 6.00 (±4.93). The difference was statistically significant (p<0.05). In group-B, mean HECSI scores at baseline and at 12th week follow up were 21.50 (±18.40) and 1.07 (±0.39). This difference also was statistically significant (p<0.05). Adverse effects were observed only in group-A. About 11.11% patients had gastrointestinal adverse events and 3.73% had increased liver enzyme. Conclusion Low dose oral Methotrexate (0.1 mg/kg body weight once weekly) is effective and safe but not a better option than topical clobetasol propionate (0.05%) in chronic hand eczema.